Effect of Disclosure Corporate Social Responsibility (CSR) to Profitability in Textile and Garment Industry Listed in Indonesia Stock Exchange in 2011-2013 - Khairudin KHAIRUDIN; Erena Dewi (Universitas Bandar Lampung (UBL), 2015)
The purpose of this study was to determine the effect of the disclosure of corporate socialresponsibility (CSR) to profability in textile and garment industry are listed on BEI in 2011 through 2013 by using purposie sampling method. There are 10 industries that respresent a sample. The method of analysis in this study is a simple regression analysis. The result of this study indicate that csr disclosure positive and significant impact on ROA and ROE and positive and significant effect on the GPM, which is an indicator of prafitability.